Synthesis and biological evaluation of isoxazolyl-sulfonamides: A non-cytotoxic scaffold active against Trypanosoma cruzi, Leishmania amazonensis and Herpes Simplex Virus. Issue 20 (1st November 2018) - da Rosa, Rafael; Zimmermann, Lara Almida; de Moraes, Milene Höehr; Schneider, Naira Fernanda Zanchett; Schappo, Alice Duarte; Simões, Claudia Maria de Oliveira; Steindel, Mario; Schenkel, Eloir Paulo; Bernardes, Lílian Sibelle Campos
Graphical abstract: Highlights: Synthesis and characterization of 20 isoxazolyl-sulfonamides are reported. The compounds were active against T. cruzi, L. amazonensis, and HSV-1. Druglikeness evaluation showed potential for further pre-clinical development. Abstract: In this study we report the synthesis, characterization, biological evaluation, and druglikeness assessment of a series of 20 novel isoxazolyl-sulfonamides, obtained by a four-step synthetic route. The compounds had their activity against Trypanosoma cruzi, Leishmania amazonensis, Herpes Simplex Virus type 1 and cytotoxicity evaluated in phenotypic assays. All compounds have drug-like properties, showed low cytotoxicity and were promising regarding all other biological activities reported herein, especially the inhibitory activity against T. cruzi . The compounds8 and16 showed significant potency and selectivity against T. cruzi (GI50  = 14.3 µM, SI > 34.8 and GI50  = 11.6 µM, SI = 29.1, respectively). These values, close to the values of the reference drug benznidazole (GI50  = 10.2 µM), suggest that compounds8 and16 represent promising candidates for further pre-clinical development targeting Chagas disease.